The Sun Down Motel - St. James, Simone (New York, N.Y. : Berkley, 2020)
Upstate New York, 1982. Viv Delaney wants to move to New York City, and to help pay for it she takes a job as the night clerk at the Sun Down Motel in Fell, New York. But something isn't right at the motel, something haunting and scary. Upstate New York, 2017. Carly Kirk has never been able to let go of the story of her aunt Viv, who mysteriously disappeared from the Sun Down before she was born. She decides to move to Fell and visit the motel, where she quickly learns that nothing has changed since 1982. And she soon finds herself ensnared in the same mysteries that claimed her aunt.
Keywords: Missing persons -- Fiction; Motels -- Fiction; Secrecy -- Fiction; Upstate New York (N.Y.) -- Fiction; Thrillers (Fiction)